2012
DOI: 10.1111/j.1440-1681.2012.12003.x
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase‐2 inhibition by temocapril and its important role in peritoneal transport

Abstract: 1. Matrix metalloproteinase (MMP)-2 plays an important role in tissue remodelling during peritoneal injury caused by peritoneal dialysis (PD), but MMP-2 inhibitors have not yet been used clinically. Recently, it was reported that captopril, an angiotensin-converting enzyme inhibitor (ACEI), can inhibit MMP-2. 2. To investigate the potential usefulness of ACEI during PD, the molecular interaction between the MMP-2 active site and the active form of temocapril (temocaprilat) was investigated using molecular mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…and the conclusion was confirmed by a multicenter study in The Netherlands [41]. Renin-angiotensin system inhibition and peroxisome proliferator-activated receptor agonist have also played a role in EPS therapy, and studies have shown that they can inhibit the activity of MMP-2 in peritoneal dialyzate and alleviate the accumulation and fibrosis of extraperitoneal matrix to some extent [42][43][44]. Perhaps MMP-2 is not only a diagnostic biomarker but also a potential therapeutic target.…”
Section: Future Directionsmentioning
confidence: 88%
“…and the conclusion was confirmed by a multicenter study in The Netherlands [41]. Renin-angiotensin system inhibition and peroxisome proliferator-activated receptor agonist have also played a role in EPS therapy, and studies have shown that they can inhibit the activity of MMP-2 in peritoneal dialyzate and alleviate the accumulation and fibrosis of extraperitoneal matrix to some extent [42][43][44]. Perhaps MMP-2 is not only a diagnostic biomarker but also a potential therapeutic target.…”
Section: Future Directionsmentioning
confidence: 88%